Phenolics profiles in Marquette juice and wine were not affected by grapevine plant growth regulators applications - Alexander Gapinski; Aude Watrelot (OENO One, 2025)
Red wines made from interspecific cold-hardy grape cultivars, such as Marquette, often have lower tannin concentrations compared to those made from Vitis vinifera, which can result in undesirable qualities like poor colour stability and oxidative aromas. To address this, various viticultural practices have been explored, including nitrogen fertilisation and plant growth regulators, to enhance phenolic content and wine quality. This study aimed to evaluate the effects of foliar phenylalanine (Phe) and prohexadione calcium (ProCa) treatments on tannin and iron-reactive phenolic (IRP) concentrations in Marquette grape juice and wine. Despite significant interaction effects between year and treatments (ProCa, Phe), the treatments themselves did not seem to have a strong impact on either IRP or tannin concentrations. This suggests that, at the current application rates, the environmental conditions play a more dominant role than the treatments.